2019
DOI: 10.1103/physreve.99.032301
|View full text |Cite
|
Sign up to set email alerts
|

Mobility helps problem-solving systems to avoid groupthink

Abstract: Groupthink occurs when everyone in a group starts thinking alike, as when people put unlimited faith in a leader. Avoiding this phenomenon is a ubiquitous challenge to problem-solving enterprises and typical countermeasures involve the mobility of group members. Here we use an agent-based model of imitative learning to study the influence of the mobility of the agents on the time they require to find the global maxima of NK-fitness landscapes. The agents cooperate by exchanging information on their fitness and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…So, we choose the linear size of the square box as M/w. Since the effective area of one site is 1/w, we adopt the linear size 1/ √ w as the spatial scale to measure all distances in our study [39]. In this way, the network properties do not depend on the linear size of the square box and are uniquely defined by the radius r measured in units of 1/ √ w. As any constant value for w works, we set w = 1.0 so the linear size of the square box becomes √ M , and the radius is a dimensionless number.…”
Section: B Random Geometric Graph: Rggmentioning
confidence: 99%
“…So, we choose the linear size of the square box as M/w. Since the effective area of one site is 1/w, we adopt the linear size 1/ √ w as the spatial scale to measure all distances in our study [39]. In this way, the network properties do not depend on the linear size of the square box and are uniquely defined by the radius r measured in units of 1/ √ w. As any constant value for w works, we set w = 1.0 so the linear size of the square box becomes √ M , and the radius is a dimensionless number.…”
Section: B Random Geometric Graph: Rggmentioning
confidence: 99%
“…Thus, the initial disposition of the agents corresponds to the classic random geometric graph originally introduced to model wireless communication networks [21]. As pointed out, this graph was successfully used as a face-to-face network in the modeling of the dynamics of human interactions [20] as well as in the study of the effects of random motility on cooperative problem-solving systems [22].…”
Section: Modelmentioning
confidence: 99%
“…Moreover, it also allows for implementing collective adaptation as a process differing from just the aggregation of individual learning dynamics. For example, by autonomously forming and recurrently reorganizing teams, a continuous process of collective adaptation emerges by reconsidering the role of the current members of the team against other potential members with different capabilities [8]. A significant branch of the previous literature concerning team self-organization has implemented auction-based mechanisms for team formation, in which an auction is held and the highest bidders are selected to form the team [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that individual learning is beneficial for task performance, but only up to a threshold [11,13]. Moreover, researchers argue that recurrent team self-organization can be harmful to performance in certain circumstances [8]. This is related to the exploration vs exploitation dilemma, which states that individuals should adequately balance searching for new solutions (i.e., exploration) against building on the solutions already at their disposal (i.e., exploitation) [13].…”
Section: Introductionmentioning
confidence: 99%